Coccolith dissolution versus productivity changes during the Plio-Pleistocene (3.14?1.80 MA) in the South Atlantic (ODP site 1090) - Ballegeer, Anne-Marie Clara; Flores Villarejo, Jos? Abel; Sierro S?nchez, Francisco Javier; Rigual Hern?ndez, Andr?s Salvador (Palaeogeography, Palaeoclimatology, Palaeoecology, 2022)
[EN] Calcareous nannofossil assemblages and fragmentation ratios of two coccolithophore species (Coccolithus pelagicus and Calcidiscus leptoporus) were analysed in samples from ODP Site 1090, South Atlantic (42? 54.8? S, 8? 53.9? E), to obtain valuable insights into the paleoceanographic evolution and carbonate preservation trends during the late Pliocene and Early Pleistocene (3.14?1.80 Ma). Coccolithophore species were identified in a total of 232 samples. Calcareous nannofossil counts revealed shifts in the assemblages that can be correlated with the climatic evolution of the Southern Ocean. Between 3.2 and 2.85 Ma, i.e. during the mid-Pliocene Warmth, the assemblage was dominated by small Gephyrocapsa, a group of species typically associated with upwelling conditions. The dominance of the opportunistic small Gephyrocapsa group can be linked to a more intense mixing of the upper water column most likely due to the more southward position of the Subtropical Front (STF) compared with its present position. After 2.85 Ma, a gradual increase in the cold water species C. pelagicus marked a progressive cooling of the South Atlantic coupled with a northward shift of the (STF). The changes in the assemblage composition co-varied with the ?18O record. Periods with isotopically heavier values (glacial) were dominated by C. pelagicus and periods with lighter values (interglacial) were dominated by very small reticulofenestrids (VSR; <3 ?m). After 2.7 Ma, an intensification of the glacial-interglacial patterns of C. pelagicus and VSR was registered. The interval between 2.44 and 2.34 Ma was characterised by low abundance of C. pelagicus and higher biodiversity which are interpreted to be due to a temporal southward movement of the STF interrupting the previously registered cooling. After 2.0 Ma, the decreasing abundance of C. pelagicus suggests a slowdown of the relatively intense cooling registered since 2.7 Ma. The fragmentation ratios of C. pelagicus and C. leptoporus suggest moderate preservation along our ...